Extended postoperative thromboprophylaxis after pancreatic resection for pancreatic cancer is associated with decreased risk of venous thromboembolism in the minimally invasive approach. Issue 3 (11th November 2022) - Sood, Divya; Kuchta, Kristine; Paterakos, Pierce; Schwarz, Jason L.; Rojas, Aram; Choi, Sung H.; Vining, Charles C.; Talamonti, Mark S.; Hogg, Melissa E.
Abstract: Background: Pancreatic ductal adenocarcinoma (PDAC) is associated with increased venous thromboembolism (VTE). We sought to compare rates of bleeding complications and VTE in patients receiving extended postoperative thromboprophylaxis (EPT) to those who did not, and identify risk factors for VTE after pancreatectomy for PDAC. Methods: This is a retrospective review of pancreatectomies for PDAC. EPT was defined as 28 days of low molecular weight heparin. Multivariable analysis (MVA) was performed to identify independent risk factors of VTE. Results: Of 269 patients included, 142 (52.8%) received EPT. Of those who received EPT, 7 (4.9%) suffered bleeding complications, compared to 6 (4.7%) of those who did not ( p  = 0.938). There was no significant difference in VTE rate at 90 days (2.8% vs. 2.4%, p  = 0.728) or at 1 year (6.3% vs. 7.9%, p  = 0.624). On MVA, risk factors for VTE included worse performance status, lower preoperative hematocrit, R1/R2 resection, and minimally invasive (MIS) approach. Among those who received EPT, there was no difference in VTE rate between MIS and open approach. Conclusions: EPT was not associated with a difference in VTE risk or bleeding complications. MIS approach was associated with a higher risk of VTE; however, this was significantly lower among those who received EPT.